THE IDEOLOGICAL, INSTITUTIONAL, AND PERSONAL TRAJECTORIES OF THE ISRAELI RIGHT: REVISIONIST ZIONISM, THE LIKUD PARTY, AND BINYAMIN NETANYAHU (Third Sector Social Economic Review, 2023)
Israeli politics experienced significant institutional and ideological developments under the hegemony of left-wing politics up until 1977. This period came to an end with the 1977 elections, and after 28 years of left-wing rule, the right-leaning Likud Party and its leader Menachem Begin came to power. Examining the social, elite, institutional, and intellectual foundations of this critical transformation in Israeli politics is crucial for understanding the processes that took place. It is necessary to scrutinize the origins of the Revisionist Movement, which remained marginalized and non-mainstream during Israel's founding period but has become the dominant political line in Israeli politics today.This article describes the Israeli right on three different levels: ideological, institutional, and personal. At the ideological level, the core ideas and formation processes of Revisionist Zionism, the fundamental ideology of the Israeli right, are examined under the leadership of Ze'ev Jabotinsky. This ideology, unlike traditional approaches of Zionist thought, focuses on the establishment of a more nationalist and powerful Jewish state. At the institutional level, the article analyzes the institutionalization of Revisionist Zionism ideology under Menahem Begin's leadership through the Likud Party. The rise of the Likud Party represents a profound change in Israeli politics, leading to the adoption of a more aggressive stance on foreign policy and security issues. At the personal level, the article focuses on the development and political strategies of the institutionalized Likud Party under the leadership of Binyamin Netanyahu. Netanyahu's leadership has been at a critical juncture in shaping Israel's settlement policies in the occupied West Bank and its international relations. The article evaluates the intertwined and cumulative formation of the Israeli right in these three areas of transformation within the context of founding elites (Jabotinsky, Begin, and Netanyahu) and critical historical events.
Keywords: Israeli Right; Revisionist Zionism; Ze’ev Jabotinsky; Menachem Begin; Binyamin Netanyahu